Early detection and manifestation of leukemia in the oral cavity of the child: Deteksi dini dan manifestasi leukemia pada rongga mulut anak - Yayah Inayah; Sumintarti; Sherly Horax; Fajriani; Marhamah (Makassar Dental Journal PDGI Makassar, 2021)
Cancer is a chronic disease and is the third leading cause of death in children aged 1-14 years. About one third of cancer in child-ren is leukemia with an incidence of 9 cases per 100,000 population. Leukemia is a malignancy of blood cells originating from the bone marrow and can occur in children and adults. Early detection of oral lesions is very important for the prevention and treatment of complications that may arise during therapy, a better prognosis, lower morbidity and mortality for that disease. Oral manifestations of leukemia are gingival enlargement and spontaneous bleeding, oral ulceration, petechiae, hematoma and pale mucosa. Oral lesions occur in both acute and chronic forms of all types of leukemia and are more common in the acute stage. Dental care for patients with leukemia should be focused on preventing injury, local control of gingival bleeding by re-moving the biofilm, and prevention of oral infection. Oral hygiene by brushing teeth, use of fluoride, and a non-cariogenic diet should also be emphasized during treatment.